Answer:
x = 3, x = 4
for all the three fill in the blanks.
Explanation:
given
m(x) = (2x-6)(x-4)
given
m(x) = 0
thus
(2x-6)(x-4) = 0
it is possible when
either (2x-6) = 0 or (x-4) = 0
as 0 * any number = 0
thus,
2x-6 = 0
=> 2x = 6
=> x = 6/2 = 3
x- 4 = 0
x = 4
Thus , for first question
x = 3, x = 4
____________________________________________
In the second problem, we have to find point on x axis where graph m intersects it.
it will happen when y = 0 , as when y is 0 , then point lies on x axis
we know that y = m(x)
thus, m(x) should be equal to 0
m(x) = (2x-6)(x-4) = 0
Again it will solved as above and value of x will be same as found above
x = 3, x = 4
___________________________________________________
Given that zeroes of function are where m(x) = 0
m(x) = (2x-6)(x-4) = 0
Again it will solved as solved in the first problem and value of x will be same as found above
x = 3, x = 4